Defining Freeway Design Capacity Based on Stochastic Observations. Issue 15 (December 2018) - Shojaat, Siavash; Geistefeldt, Justin; Parr, Scott A.; Escobar, Luis; Wolshon, Brian
The estimation of capacity as a parameter to assess traffic flow performance on freeway facilities has received considerable attention in the literature. Despite the general acceptance of the stochastic notion of capacity, limited research has been conducted on how to select a single representative design value from a capacity distribution function. This paper reports the results of an empirical comparison between conventional capacity estimates and those obtained by maximizing the sustained flow index (SFI) for 19 U.S. freeway sections. The SFI is defined as the product of the traffic volume and the probability of survival at this volume. The capacity of each cross-section was estimated by analyzing the speed–flow relationship and applying methods for stochastic capacity analysis. The results show that the optimum volumes obtained by maximizing the SFI estimated in 5-minute intervals correspond well to the 15% probability of breakdown proposed in the Highway Capacity Manual 6 th Edition to estimate the capacity from field data. From these results, it was concluded that maximizing the SFI can be considered a preferred approach to estimate a single, representative value of freeway capacity.